The ecology and epidemiology of Ross River and Murray Valley encephalitis viruses in Western Australia: Examples of One Health in Action - Mackenzie, John; Lindsay, M.; Smith, D.; Imrie, A. (Oxford, 2017)
© The Author 2017. Published by Oxford University Press on behalf of Royal Society of Tropical Medicine and Hygiene. Arboviruses are maintained and transmitted through an alternating biological cycle in arthropods and vertebrates, with largely incidental disease in humans and animals. As such, they provide excellent examples of One Health, as their health impact is inextricably linked to their vertebrate hosts, their arthropod vectors and the environment. Prevention and control requires a comprehensive understanding of these interactions, and how they may be effectively and safely modified. This review concentrates on human disease due to Ross River and Murray Valley encephalitis viruses, the two major arboviral pathogens in Australia. It describes how their pattern of infection and disease is influenced by natural climatic and weather patterns, and by anthropogenic activities. The latter includes human-mediated environmental manipulations, such as water impoundment infrastructures, human movements and migration, and community and social changes, such as urban spread into mosquito larval habitats. Effective interventions need to be directed at the environmental precursors of risk. This can best be achieved using One Health approaches to improve collaboration and coordination between different disciplines and cross-sectoral jurisdictions in order to develop more holistic mitigation and control procedures, and to address poorly understood ecological issues through multidisciplinary research.